Differences in Levels of Autonomy and Fitness of Elementary School Students Based on Transportation Mode - Muhammad Abdul Aziz Santoso; Ali Maksum; Made Pramono (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
It is known that in addition to biking and walking, many students who prefer to be taken by parents or use an online motorcycle taxi to go to school. Generally, going to school using a bicycle is an alternative means of transportation that is preferred, but because of the lack of parking lots of students who ultimately prefer to be picked up and dropped off. In addition, parenting parents who are too protective of children to require children to be picked up when going to school also indirectly have an unfavorable impact on the child's level of fitness and independence. Whereas for elementary school children, the level of fitness and independence are things that must be developed for their future survival. Children must understand the importance of physical activity and implement it in their lives. For example, children who go to school, they must be more able to think about how to move their body to get to school rather than just relying on the transfer of parents. By walking to school, will increase physical activity of children. Therefore, researchers are then interested in conducting further research. The results of this study are that there are significant differences in the fitness variable of transportation used with a significance level of 0,000 and an F value of 21,914 with a mean difference of 73,393. Walking is the most dominant factor to improve fitness compared to cycling and parents take a motorbike ride to and from school. As for the independence variable there is no significant difference in the mode of transportation used with a significance value of 0.414 with an F value of 0.890. The conclusion of the research is the use of modes of transportation to the right school can increase children's fitness. Walking is the best transportation to improve fitness then followed by cycling and parents take a ride on a motorcycle. However, to increase a significant independence, it is still not possible to use transportation mode selection because parental care is the determining factor for children's independence other than the education system in schools and the surrounding environment.